Inside Back Cover: Electrochemical Aspects of Mass Spectrometry: Atmospheric Pressure Ionization and Ambient Ionization for Bioanalysis (ChemElectroChem 4/2017). Issue 4 (16th March 2017) - Yuill, Elizabeth M.; Baker, Lane A.
Abstract : The Inside Back Cover picture highlights how interesting opportunities for new analytical and physical measurements can arise through the combination (or "mixing!") of electrochemical and mass spectrometry techniques. Recent advances are described in the field of combined electrochemical and mass spectrometric measurements for atmospheric pressure ionization and ambient ionization, especially in the quest to analyze biological samples. More information can be found in the Review by E. Yuill and L. A. Baker onpage 806 in Issue 4, 2017 (DOI:10.1002/celc.201600751 ).